Effect of ethanolic extraction, thermal vacuum concentration, ultrafiltration, and spray drying on polyphenolic compounds of tropical highland blackberry (Rubus adenotrichos Schltdl.) by-product - Quirós Blanco, Ana María (2019)
Tropical highland blackberry by-product (BBP) has high amounts of polyphenols including ellagitannins (ET) and anthocyanins (ATC). Information of the effect of different operations on ET is scarce. In this study, pseudo-first and first order kinetic models and response surface methodology were applied to optimize the extraction of polyphenols from BBP using ethanol, a food grade solvent. Retention of total polyphenols, ET and ATC was analyzed considering their contents before and after the application of thermal vacuum concentration, ultrafiltration, and spray drying. The optimal conditions for extraction were: a 3.4 solvent/BBP ratio, 57.1% ethanol, 60.0°C, and 120 min extraction time. Thermal vacuum concentration showed a higher retention of ET. A higher purity of ET was accomplished with ultrafiltration. These results provide the basis for further research on the development of a powder enriched with polyphenols, mainly ET, from BBP for food and pharmacological purposes.